2021
DOI: 10.18178/ijesd.2021.12.5.1330
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Modeling of nFe0/Cu-PRB Design for Cr(VI) Removal from Groundwater

Abstract: Hexavalent chromium is one of the highly toxic heavy metals which could lead to severe health issues when it is discharged into aquifers as industrial wastewater. In the current study nFe0/Cu was successfully employed in PRB technology for Cr(VI) removal from groundwater. Batch and column experiments confirmed the high reactive performance of nFe0/Cu towards Cr(VI) removal by around 85% removal efficiency. The main pathways for Cr-species removal by nFe0/Cu were determined as the reduction of Cr(VI) to Cr(III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 35 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…The ZVI surface is plated with another metal with high reduction potential (such as copper, platinum, and nickel) to form bimetallic material, which act as galvanic cells during the reaction to speed up the reaction rate. The bimetallic system composed of nZVI can reduce the agglomeration between nZVI and the activation energy during the reaction, thereby increasing the reduction rate (Maamoun et al, 2021). Shubair et al (2018) demonstrated that the removal mechanism of cesium by nZVI and nZVI/Cu is mainly chemical adsorption, with a removal rate of more than 99%.…”
Section: Composite Materials Related To Zero-valent Iron 2311 Bimetal...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ZVI surface is plated with another metal with high reduction potential (such as copper, platinum, and nickel) to form bimetallic material, which act as galvanic cells during the reaction to speed up the reaction rate. The bimetallic system composed of nZVI can reduce the agglomeration between nZVI and the activation energy during the reaction, thereby increasing the reduction rate (Maamoun et al, 2021). Shubair et al (2018) demonstrated that the removal mechanism of cesium by nZVI and nZVI/Cu is mainly chemical adsorption, with a removal rate of more than 99%.…”
Section: Composite Materials Related To Zero-valent Iron 2311 Bimetal...mentioning
confidence: 99%
“…Copper can promote the electron transfer of Fe 0 and the generation of Fe 2+ , thereby accelerating Cr(VI) removal. With the remove of Cr(VI) by the bimetallic system composed of nZVI/Cu as an example, the chemical reaction formula is as follows (Maamoun et al, 2021):…”
Section: Composite Materials Related To Zero-valent Iron 2311 Bimetal...mentioning
confidence: 99%
“…Fe 0 is one of the most widely used reactive nanomaterials in water treatment applications within the last decade. The unique features of Fe 0 , represented in the nano size, high redox potential, coreshell structure, and high specific surface area, enables it to remove most of the soluble contaminants via several removal mechanisms (e.g., sorption, precipitation, coprecipitation, and reduction) [42][43][44][45][46]. As presented in Table 2, the use of iron-based sorbents in the removal of radionuclides from water has been intensively reported in the literature, owing to the great sorption abilities of such materials [47].…”
Section: Nanomaterials Sorbents 221 Iron-basedmentioning
confidence: 99%
“…Despite the superb characteristics of Fe 0 nanoparticles, for instant, high reactivity, high surface area, and multiple elimination mechanisms, they still have several drawbacks which restrict their ability to remediate antibiotics from water (Falyouna et al 2019;Maamoun et al 2021a). Fast surface oxidation, agglomeration and insignificant oxidation capacity are the main weaknesses of Fe 0 nanoparticles and various approaches were embraced to tackle these limitations (Mokete et al 2020;Maamoun et al 2021b). The pervious researchers adopted numerous techniques to improve the performance of Fe 0 nanoparticles towards the elimination of CIP from water such as addition of Fenton reagent (i.e.…”
Section: Introductionmentioning
confidence: 99%